Comparative Analyses of Dynamic Transcriptome Profile of Heart Highlight the Key Response Genes for Heat Stress in Zhikong Scallop Chlamys farreri - Xinyuan Wang; Zujing Yang; Cheng Peng; Haitao Yu; Chang Cui; Qiang Xing; Jingjie Hu; Zhenmin Bao; Xiaoting Huang (MDPI AG, 2024)
Heat stress resulting from global climate change has been demonstrated to adversely affect growth, development, and reproduction of marine organisms. The Zhikong scallop (Chlamys farreri), an important economical mollusk in China, faces increasing risks of summer mortality due to the prolonged heat waves. The heart, responsible for transporting gas and nutrients, is vital in maintaining homeostasis and physiological status in response to environmental changes. In this study, the effect of heat stress on the cardiac function of C. farreri was investigated during the continuous 30-day heat stress at 27 °C. The results showed the heart rate of scallops increased due to stress in the initial phase of high temperature exposure, peaking at 12 h, and then gradually recovered, indicating an acclimatization at the end of the experiment. In addition, the levels of catalase (CAT), superoxide dismutase (SOD), and total antioxidant capacity (T-AOC) exhibited an initial increase followed by recovery in response to heat stress. Furthermore, transcriptome analysis of the heart identified 3541 differentially expressed genes (DEGs) in response to heat stress. Subsequent GO and KEGG enrichment analysis showed that these genes were primarily related to signal transduction and oxidative stress, such as the phosphatidylinositol signaling system, regulation of actin cytoskeleton, MAPK signaling pathway, FoxO signaling pathway, etc. In addition, two modules were identified as significant responsive modules according to the weighted gene co-expression network analysis (WGCNA). The upregulation of key enzymes within the base excision repair and gap junction pathways indicated that the heart of C. farreri under heat stress enhanced DNA repair and maintained cellular integrity. In addition, the variable expression of essential signaling molecules and cytoskeletal regulators suggested that the heart of C. farreri modulated cardiomyocyte contraction, intracellular signaling, and heart rate through complex regulation of phosphorylation and calcium dynamics in response to heat stress. Collectively, this study enhances our understanding of cardiac function and provides novel evidence for unraveling the mechanism underlying the thermal response in mollusks.